Principles of microwave technology - Harsany, Stephen C (Prentice Hall, 1997)
This text offers comprehensive coverage of microwave topics in one volume. It provides descriptions, analysis and up-to-date specific applications in radar and communications including the new wireless technologies. This edition includes coverage of microwave topics, a software tutorial (on an accompanying diskette) with detailed information on thermionic microwave devices (especially relevant in satellite technology), and an applications chapter on new and emerging microwave technology. All maths is kept at the algebra or simple trigonometry levels and the book assumes a familiarity with alternating current theory.